The Christmas Eve tree - Huddy, Delia; Sutton, Emily (Somerville, Massachusetts : Candlewick Press, 2016)
Late on Christmas Eve, a little fir tree is the only one left for sale when a homeless boy, who doesn't seem to mind that it's neither tall nor straight, decorates it with candles, and the tree finds itself at the center of a magical Christmas Eve.
Keywords: Christmas trees -- Fiction; Christmas -- Fiction; Christmas trees -- Fiction; Christmas -- Fiction